How sensitive are epiphytic and epixylic cryptogams as indicators of forest naturalness? Testing bryophyte and lichen predictive power in stands under different management regimes in the Białowieża forest - Janusz Czerepko (Elsevier, 2021)
The aim of this study was to test the sensitivity of epiphytic and epixylic bryophytes and lichens as indicators of forest naturalness, by comparing their diversity patterns with forest structural, compositional and historical features associated with different management/protection regimes and protection time spans. The study was carried out in the Białowieża Forest (Poland). Out of 1370 pre-existing inventory plots established all across the Polish part of the Białowieża Forest, we randomly selected 10 plots for each of the 18 plot aggregation groups resulting from the combination of 3 management/protection regimes and 6 habitat types, for an overall number of 180 plots. At each of them, we carried out bryophyte and lichen sampling on four substrates (coarse woody debris – CWD, standing dead trees, stumps, living trees). The management/protection regimes exemplifying the gradient of forest naturalness were: the 100 years-old Białowieża National Park (BNP), a set of more recently established nature reserves and managed forests. We tested differences in mean species richness values among management/protection regimes, protection time spans, habitat types and stand age classes by analysis of variance and calculated coefficients of correlation with 45 selected structural and compositional features of forest stands. Differences in species composition of epiphytic and epixilic bryophytes and lichens among management/protection regimes were tested by ordination methods. Lastly, we compared frequency of red-listed species and primeval forest relics among management/protection regimes. Species richness of lichens was significantly correlated with the degree of forest naturalness assessed by structural and historical features along the naturalness gradient, with the highest number of species recorded in BNP and the lower in managed stands, while bryophyte number did not exhibit a clear dependence on the management regimes. Relic species of primeval forests and red-listed species occurred with significantly higher frequency in protected areas than in managed forests for both lichens and bryophytes, with the highest frequency observed in BNP for lichens and in nature reserves for bryophytes. Volume of deadwood, particularly of CWD in advanced decays stage, species richness of undergrowth vascular plants, tree layer diversity, shrub cover and herb layer cover exhibited the strongest correlation with cryptogam species richness and cover on the various substrates. Response to light availability strongly differenciated bryophyte and lichens optimal niches. The results of this study clearly show that cryptogams, and lichens in particular, are indeed reliable ecological indicators of forest status, since they sensibly intercepted the environmental changes observable along the tested naturalness gradient.